Head protection for electric micromobility - Serra, Gabriel Ferreira (2023)
E-micromobility (EMM) has recently appeared as a practical solution for shortdistance commuters, and it is growing at upsetting rates thanks to the introduction of sharing services. In fact, urban mobility has drastically changed over the last decade, and electric mobility and micromobility changed the panorama in larger metropolises, given their accessibility, large availability, and the potential to be a time saver in short trips and a potentially sustainable alternative in particular scenarios. The downside of portable e-transportation is the rapid increase in injuries and fatalities. Focusing on standing e-scooters, head injuries are becoming one of the most common as shown by research conducted in different urban emergency departments, alongside bone fractures, skin abrasions, and lacerations. The evolution of safety measures and regulations did not keep pace with such a drastic change in mobility trends. This is evident considering how some countries are struggling with vehicle categories and regulations for helmet use and testing. In this work, the reasons behind the low rates of helmet use are explained and a design-based approach is taken towards the main problem associated with it: the lack of convenience. Besides the inadequacy of existing helmets for the sharing systems, there is also a problem with their sustainability since not only the components are difficult to separate but also some of them, such as the liner, are usually made of expanded polystyrene (EPS), a foam that is not recyclable. Literature has proven that cork, a natural cellular material, has a great potential to replace synthetic foams for applications that involve impact protection. Therefore, experimental campaigns involving dynamic impact tests have been conducted on cork and other new promising materials with energy absorption capabilities, such as shear thickening fluids, to evaluate the best combinations for replacing the standard materials used by the helmet industry. Afterwards, a validation of the drop tests has been done in Abaqus, which allowed for a numerical simulation of the EN 1078 standard’s impact attenuation test with a generic helmet on a headform in order to verify the optimal thickness of the liner. The final result is an innovative helmet that can be flattened to about the size of a laptop when not in use and be easily stored in a backpack. Furthermore, its carbon footprint is 42% lower than of a standard helmet, besides being able to be fully disassembled and recycled. It represents a big innovation for the helmet industry not only in aesthetical and functional aspects, but also regarding sustainability, having the concept met three of the seventeen goals established by the UN 2030 agenda for sustainable development.